Trace Element Content and Food Safety of Traditional Crackers (Kerupuk) Collected from Java Island, Indonesia - Indah Kusmartini; Diah Dwiana Lestiani; Syukria Kurniawati; Endah Damastuti; Natalia Adventini; Woro Yatu Niken Syahfitri; Dyah Kumala Sari; Djoko Prakoso Dwi Atmodjo; Muhayatun Santoso (Universitas Gadjah Mada, 2022)
In this study, trace elements in crackers were determined using Instrumental Neutron Activation Analysis (INAA) to assess their intake, food safety, and health contribution. The 62 samples of crackers were collected and purchased from local markets in five provinces of Java during 2013–2014. The validation method was performed using SRM Wheat Flour 1567a, with 80–110% accuracy (% recovery) and precision less than 10% (% RSD). The concentration of trace elements such as Cr, Co, Fe, and Zn was analyzed and found in the range of 0.03–1.4, 0.01–0.32, 14.49–85.70, 0.15–17.26 µg/g, respectively. Daily intake of elements in crackers contributes less than 1% to Recommended Dietary Allowances (RDA). Based on food safety evaluation through the calculation of Hazard Quotient, the value of Cr, Co, Fe, and Zn is less than 1, indicating that the crackers are safe for consumption and do not possess non-carcinogenic health risks due to heavy metals content. Therefore, the crackers in all Java provinces meet the current standards and are safe for consumption.